(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
General description of the basin. The basin of the Koradarya River is located in the eastern part of the Fergana Valley. Its water flows down from the southwestern slopes of the Fergana mountain range and the northern slopes of the Alay mountain range. The Fergana range rises from the northwest to the southeast. In the northwest, its height does not exceed 4000 m, while in the southeast, in the areas connected with the Alay range, it reaches nearly 5000 m. Even the mountain passes in this part of the range exceed 4000 m in height.